Уран и торий в рудах Бакчарского железорудного месторождения - Ершов В. В. Василий Владимирович; Рихванов Л. П. Леонид Петрович; Пшеничкин А. Я. Анатолий Яковлевич; Арбузов С. И. Сергей Иванович (Геохимия, 2012)
Заглавие с титульного листа